ANALISIS LARANGAN RANGKAP JABATAN MENTERI DALAM PARTAI POLITIK BERDASARKAN UNDANG -UNDANG PASAL 23 NOMOR 39 TAHUN 2008 - Fadila Muajaba Kasanah; Dian Suluh Kusuma Dewi (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2022)
Currently, Indonesia is experiencing a polemic about the existence of multiple positions by ministers in the head of a political party. In this case, a big problem arises, one of which is the abuse of power. The purpose of this research is to analyze and examine more deeply about the prohibition of concurrent ministerial positions in political parties based on Law article 23 Number 39 of 2008. The research method used by the author is library research. The purpose of this research method is to examine the object of discussion in the form of written sources in order to obtain clear data and facts by relying on various literatures that have a close relationship with the object of discussion in this study. As for this research, the researcher uses the Statute Approach. By using this legal approach, of course, Article 23 Number 39 of 2008 concerning Concurrent Ministerial Positions in Political Parties will be reviewed in order to be used as a barometer in order to provide justification for the object being studied by researchers regarding Concurrent Ministerial Positions in Political Parties. The results of this study are according to Law Article 23 Number 39 of 2008 the State Ministry discusses the prohibition of concurrent positions. However, in the implementation of Law Article 23 Number 39 of 2008 there are actually multiple interpretations of the existence of the law. In order to avoid multiple interpretations, it is necessary to give firmness. The government should review the law again, and then make improvements to the State Ministry Law. Keywords: Minister; Double job; Political parties